Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fnbeh.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Period for Prefrontal Network Configurations Underlying Psychiatric Disorders and Addiction

Abstract: The medial prefrontal cortex (mPFC) has been classically defined as the brain region responsible for higher cognitive functions, including the decision-making process. Ample information has been gathered during the last 40 years in an attempt to understand how it works. We now know extensively about the connectivity of this region and its relationship with neuromodulatory ascending projection areas, such as the dorsal raphe nucleus (DRN) or the ventral tegmental area (VTA). Both areas are well-known regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 119 publications
(122 reference statements)
1
15
0
Order By: Relevance
“…It has been hypothesized that critical periods impact the development of mood disorders such as anxiety and schizophrenia (21)(22)(23). Supporting the above-mentioned maternal separation results, we recently found that the Otx2 +/AA mice display prolonged acquisition of acoustic preference in adulthood linked to anxiolysis (20).…”
Section: Introductionsupporting
confidence: 82%
“…It has been hypothesized that critical periods impact the development of mood disorders such as anxiety and schizophrenia (21)(22)(23). Supporting the above-mentioned maternal separation results, we recently found that the Otx2 +/AA mice display prolonged acquisition of acoustic preference in adulthood linked to anxiolysis (20).…”
Section: Introductionsupporting
confidence: 82%
“…[6,7] Being able to use this knowledge and manipulate the course and duration of a CP might have an enormous therapeutic poten-tial for a variety of developmental cognitive disabilities, as well as recovery from brain injuries and stroke. [1,8,9] There is a special need to develop new models that specifically address these topics and that provide the ability to control plasticity in the adult brain.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,7 ] Being able to use this knowledge and manipulate the course and duration of a CP might have an enormous therapeutic potential for a variety of developmental cognitive disabilities, as well as recovery from brain injuries and stroke. [ 1,8,9 ] There is a special need to develop new models that specifically address these topics and that provide the ability to control plasticity in the adult brain. In this review we consider the most recent studies focusing on CPs in fruit fly Drosophila melanogaster (Figure 1) that provide new insights into regulatory mechanisms, opportunities for in vivo CP manipulations and linking them with maturation of social behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The CA1 region of the vHP in particular sends strong projections to other regions, such as the BA, hypothalamus, nucleus accumbens, and the mPFC (47)(48)(49)(50), and there is evidence that these projections process emotional behavior (51)(52)(53). In addition, impaired function in Hippocampal-prefrontal circuit has been observed in psychiatric patients including PTSD and schizophrenic subjects (54), and configurational changes in prefrontocortical inputs from Amygdala and Hippocampus have been suggested as a possible mechanism underlying psychiatric disorders (55). Furthermore, it has been reported that BDNF infusion into the PFC and HP erases fear memory (56), and engram cells of projection neurons in CA1 of vHC play a necessary and sufficient role in social memory (57).…”
Section: Fear Extinction Circuitrymentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted February 14, 2021. ; https://doi.org/10.1101/2021.02.14.431126 doi: bioRxiv preprint inputs from Amygdala and Hippocampus have been suggested as a possible mechanism underlying psychiatric disorders (55). Furthermore, it has been reported that BDNF infusion into the PFC and HP erases fear memory (56), and engram cells of projection neurons in CA1 of vHC play a necessary and sufficient role in social memory (57).…”
Section: Fear Extinction Circuitrymentioning
confidence: 99%